HUMAN CAPITAL DEVELOPMENT AND SUPPORT STRATEGY IN UZBEKISTAN - Jumaboyevich, Hojiyev Farhod (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Human capital development is a critical factor for national growth and competitiveness, influencing various sectors such as education and healthcare. Global approaches to human capital development offer diverse strategies and frameworks that can be adapted to national contexts. Specific Background: This article examines the global strategies for human capital development, with a particular focus on Uzbekistan's approach. It reviews the strategic goals and tasks outlined by Uzbekistan, especially in relation to its 2030 vision, and assesses their application across key sectors including education and healthcare. Knowledge Gap: Despite extensive research on global human capital development strategies, there is a limited understanding of how specific national strategies, such as those of Uzbekistan, are operationalized and their effectiveness in addressing sector-specific challenges. Aims: The primary aim of this article is to analyze and evaluate the global approaches to human capital development, assess the strategic goals and tasks adopted by Uzbekistan, and explore their implementation and impact across various sectors. Results: The analysis reveals that Uzbekistan’s human capital development strategy, as outlined in the Uzbekistan-2030 plan, prioritizes key areas such as education and healthcare. The implementation of these strategies has shown significant progress, although challenges remain in fully realizing their potential across all sectors. Novelty: This article provides a detailed evaluation of Uzbekistan’s human capital development strategy within the context of global approaches, offering new insights into the effectiveness of sector-specific implementations and their alignment with broader strategic goals. Implications: The findings underscore the importance of targeted human capital development strategies in achieving national growth objectives. They highlight the need for ongoing assessment and adaptation of strategies to ensure that they effectively address sectoral needs and contribute to the broader goals outlined in national development plans.